Plant Turnover and Productivity Growth in Canadian Manufacturing - Baldwin, John R.. (OECD Publishing, 2002)
Entry is important because new firms and new plants provide an important source of competition to incumbents. They are a source of new products and technologies. In this paper, we outline the size of the turnover in plants that have entered and exited the Canadian manufacturing sector over each of the last three decades - 1973-79, 1979-88 and 1988-97. We also examine the contribution of plant turnover to labour productivity growth in the manufacturing sector over the three periods. Plant turnover makes a significant contribution to productivity growth as more productive entrants replace exiting plants that are less productive. We also find that a disproportionately large fraction of the contribution of plant turnover to productivity growth is due to multi-plant or foreign-controlled firms closing down and opening up new plants. The plants opened up by multi-plant or foreign-controlled firms are typically much more productive than those opened by single-plant or domestic-controlled ...
Keywords: Science and Technology; Canada